Pembuatan Peta Berbasis Geospasial Sebagai Upaya Peningkatan Kesejahteraan Masyarakat di Desa Sejangat, Kecamatan Bukit Batu, Kabupaten Bengkalis - Putri, Diana Eka; Sri Restuti; Pitisye, Annisa Baity; Hasibuan, Arisandi; Delfi Riska Ananda; Fien Hasanah; Ikhwan Fauzan; M. Al Rafi Fajri Wiraguna; Mellia Savitri Marsyof; Voadi, Salsabilla Diva (Universitas Muhammadiyah Surakarta, 2024)
Sejangat Village is one of the villages in Bukit Batu District, Bengkalis Regency. Sejangat Village has land and village infrastructure that is quite complete. However, only a few people understand the land use and use of existing infrastructure in this village. In this era of technological progress, we are required to be able to access information quickly and in a wider scope. So a map is needed that can access the location, land use, existing facilities and infrastructure. This aims to provide village governments and communities with information and improve skills to manage regional development. The method used in making this map is field survey by service students, preparation and making of the map. This activity produces a village map which contains comprehensive information about land, location, regional boundaries, water areas, facilities and infrastructure in the village geospatially. The existence of a village map makes it possible to utilize new land and improve facilities and infrastructure. Therefore, the presentation of maps needs to be done over time to update village conditions. Apart from that, increasing the knowledge and skills of village officials regarding the management of village areas and infrastructure so that they can create a well-organized village with good administrative order in Sejangat Village, Bukit Batu District, Bengkalis Regency. Keyword :Geospatial Map, Location, Administrative